Petrography and Geochemistry of Zubair Shale Formation in Rumaila Oilfield, Southern Iraq: Implications for Provenance and Tectonic Setting - Ali, Rana Abbas (Journal of Petroleum Research and Studies, 2023)
A detailed sequential analysis which included thin section petrography, X-ray diffraction, and X-ray fluorescence was applied to investigate the mineral, chemical classifications, provenance, paleo-weathering, paleoclimate, and maturity features of such Zubair oil shale in the Rumaila oilfield in southern Iraq. In core samples and thin sections, the analyzed shales are primarily silty, flaky to subflaky, micaceous, calcareous, well-sorted, poorly cemented, and weakly to moderately compacted silt-grade sandy mudstone. According to XRD analysis, the main mineral is quartz, which is followed by kaolinite, while calcite and dolomite are less common and Illite, Illite/smectite, and pyrite are rarely abundant. Petrographic analysis of the Zubair shales revealed four lithofacies: silty clayey laminated mudstone lithofacies, mica-rich mudstone lithofacies, clay-rich siliceous mudstone lithofacies, and clay-bearing calcareous mudstone lithofacies. Major and trace element concentrations reveal that the oil shales have been formed from felsic rocks such as granodiorite, tonalite, and granite. A passive margin setting was revealed by the tectonic discrimination diagram. Weathering index values like the (CIA) chemical index of alteration, the (PIA) plagioclase index of alteration, and the (CIW) chemical index of weathering imply extensive chemical weathering in the source area. Zubair shales' K2O/Na2O ratio and (ICV) index of compositional variation are uniform with their high maturity. The compositions of mineral and trace elemental ratios, as well as the climatic index "C," indicate a warm to humid subtropical climate with deposition in a shallow oxic and dysoxic environment.